Duração razoável do trabalho no direito laboral brasileiro pela ótica do conceito de trabalho decente - Santos, Luiz Agueda (2025)
The present study aims to understand the respect for the concept of decent work by examining the realization or feasibility of the ideal of reasonable working hours, an essential element of the sub-concept of quality work. This sub-concept is understood, as a result of this research, as part of the decent work framework defended by the International Labour Organization (ILO). To this end, a review of specific national and international literature, as well as various national and international regulations, especially those produced by the ILO, is conducted in order to understand the meanings of: 1) decent work; 2) quality work; and 3) reasonable working hours. The study concludes that there is partial adherence to the concept proposed by the intergovernmental body, with a relatively limited scope of protection regarding working hours, which, however, does not extend to all workers